Studies on Phytochemicals and Inorganic Constituents of Ocimum Sanctum (Lamiaceae) Stem and Leaves: Phytochemical and Nutritional Analysis of Ocimum Sanctum Stem and Leaves (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The preliminary phytochemical analysis of ocimum sanctum (LAMIACEAE) leavesstem were studied. The nutritional analysis of this plant showed very low level of acidity (0.06) and protein 1.10 in its leaves and stem. The crude fibres were found to be maximum 12.20 and 9.80 in stem and leaves. As such its stem was nutritionally enriched in all respect with respect to leaves. The minerals analysis showed no remarkable change in the result. Although the quantities of Fe, Na and K were higher in stems than leaves. The results of phytochemical analysis were same in both stem and leaves which confirm the presence of phytochemicals like alkaloids, glycosides, flavonoids, tannins, terpenoids and saponins which have important role in traditional medicinal drug preparations.